ANALISIS PENGELOLAAN HUTAN OLEH MASYARAKAT DAYAK SIANG DI DESA MUWUN KECAMATAN TANAH SIANG KABUPATEN MURUNG RAYA KALIMATAN TENGAH - Kristian Hadinata; Hafizinanor -; Daniel Itta (Lambung Mangkurat University-Indonesia, 2021)
Murung Raya District in the middle of the island of Borneo makes this widest district in Central Kalimantan quite isolated. Population centers are separated by hills and mountains. Its natural resources are abundant and have not all been utilized, including coal and gold. This study aims to identify the ecological potential, analyze the management system and determine the performance of forest management by Dayak Siang Communities in Muwun Village, Tanah Siang Subdistrict, Murung Raya District, Central Kalimantan Province. The method used was the interpretation of satellite imagery, sampling techniques, interviews, observation, documentation and performance analysis. The performance value of Forest Areas in Muwun Village, Tanah Siang Subdistrict, Murung Raya District, Central Kalimantan, if viewed in terms of area was not good because 57 ha of natural forest has a level of performance worth 172 with less good category, then in rubber plantations and mixed plantations with an area of 217 ha with a performance value of 315 was very good with a very good category. It can be said that forest management in the Forest area in Muwun Village, Tanah Siang Subdistrict, Murung Raya District Central Kalimantan was less successful because it appeared that around 80% of the forest was ecologically very high on rubber farms and from NTFPs, natural forests have less performance value because the level of community’s awareness to maintain and manage natural forests was still minimal. This happened because they have obtained permission from the Murung Raya Regional Government for forest management on the reason that the local community considered the forest as a source of livelihood to survive.